Implementation of Inspirative Models of Guidance and Counseling Services Curriculum Independent at Inspiring School - Hendro Yulius Suryo Putro; Ali Rachman; Toni Maxitop (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
This study aims to determine the implementation of an inspirational model for Guidance and Counseling services in one of the Inspiring Schools, namely SMP Negeri 16 Banjarmasin. The research method uses descriptive qualitative. Data collection techniques using interviews, observation, and documentation. The research subjects included school principals as the Inspiring School program implementers, Grade 7 Guidance, Counseling teachers as independent curriculum implementers, and two learning committee teachers. Data were analyzed through three stages: data reduction, presentation, and conclusion. The study results show that implementing Guidance and Counseling using the Inspirational BK service model shows that the collaboration between Guidance and Counseling teachers and subject teachers is more intensive when implementing the independent curriculum. Guidance and Counseling service values ​​refer to the profile of Pancasila students. Therefore, guidance and counseling teachers are also involved in planning and implementing projects to strengthen Pancasila student profiles. However, the teacher's understanding of the achievements of Guidance and Counseling services in phase D needs to be further strengthened. Barriers experienced due to teacher training in the implementation of inspirational service models are still limited, so Guidance and Counseling teachers try to independently develop the implementation of inspirational guidance and counseling service models. References to implementing Guidance and Counseling services in the independent curriculum in Inspiring schools from independent teaching platforms and other sources are also limited.